If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+36=5x+4
We move all terms to the left:
3x+36-(5x+4)=0
We get rid of parentheses
3x-5x-4+36=0
We add all the numbers together, and all the variables
-2x+32=0
We move all terms containing x to the left, all other terms to the right
-2x=-32
x=-32/-2
x=+16
| 9=7y/2 | | -s+6=-10 | | 4+3(x+)=10 | | 6x-11=9x-5 | | y=2.50+30 | | 2.5x+3x+200+175=500 | | 2.5x+3x+200+175=50 | | 9=(7y/2) | | 8+5w=7w | | 0.75(3x-5)=0.5(2x+4) | | 2.5x-200=3x-175 | | 16.202+p=-9.6 | | 1x+9=10-5x | | 2.5x+200=3x+175 | | 9(w-2)=4 | | 9x+9=9-2x | | 2.5x+175=3x+200 | | 2x2-6=42 | | w+8/2=6 | | n-28=0 | | -6(2x+1)-3(x-4=-15x+1 | | 2x+8=6-3x | | K=10t+19 | | -6(2x+1)-3(x-4=-15+1 | | k/4+7=11 | | -1=3(y-2)-8y | | 14m-(-7m-3)=m | | j/3-10=-9 | | 3(3x+4)-5=9x-2 | | 0.2w=400 | | X-19=3x-11 | | 2x=16=10x |